Impact of spontaneous donor hypothermia on graft outcomes after kidney transplantation - Schnülle, Peter; Mundt, Heiko; Drüschler, Felix; Schmitt, Wilhelm; Yard, Benito A.; Krämer, Bernhard; Benck, Urs Tobias (American journal of transplantation, 2018)
A previous donor intervention trial found that therapeutic hypothermia reduced delayed graft function (DGF) after kidney transplantation. This retrospective cohort study nested in the randomized dopamine trial (ClinicalTrials.gov identifier: NCT000115115) investigates the effects of spontaneous donor hypothermia (core body temperature <36°C) on initial kidney graft function, and evaluates 5-year graft survival. Hypothermia assessed by a singular measurement in the intensive care unit 4-20 hours before procurement was associated with less DGF after kidney transplantation (odds ratio [OR] 0.56, 95% confidence interval [CI] 0.34-0.91). The benefit was greater when need for more than a single posttransplant dialysis session was analyzed (OR 0.48, 95%CI 0.28-0.82). Donor dopamine ameliorated dialysis requirement independently from hypothermia in a temporal relationship with exposure (OR 0.93, 95%CI 0.87-0.98, per hour). A lower core body temperature in the donor was associated with lower serum creatinine levels before procurement, which may reflect lower systemic inflammation and attenuated renal injury from brain death. Despite a considerable effect on DGF, our study failed to demonstrate a graft survival advantage (hazard ratio [HR] 0.83, 95%CI 0.54-1.27), whereas dopamine treatment was associated with improved long-term outcome (HR 0.95, 95%CI 0.91-0.99 per hour).